Upaya Meningkatkan Kemampuan Pemecahan Masalah Matematis melalui Pendekatan Realistik Siswa Kelas VIII MTs Pondok Pesantren Saifullah T.A 2021/2022 - Ranie Julia; Ramadhani; Hizmi Wardani (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2022)
This study aims to improve mathematical problem-solving skills through a realistic approach, to determine the Mastery of learning mathematics and student responses to learning with a realistic approach. This type of research is classroom action research with the subject of class VIII MTs Saifullah Islamic Boarding School, carried out in 2 cycles. Data retrieval is done by testing problem-solving skills and student responses. The results showed that problem-solving ability has increased. This can be seen from the classical completeness of the student's problem-solving ability test from the initial examination. Cycle 1 and cycle 2 are 5 (25%) students who complete the initial test, 12 (60%) students who complete cycle 1, and 17 (85%) students who complete cycle 2. The conclusion is the students' mathematical problem-solving abilities have increased through a realistic approach, Mastery of mathematics students' learning has increased through a realistic approach, and student responses to learning with a realistic approach to number pattern material are very good.